Factors Associated with Mothers Health Seeking Behavior among Newborn Illness - Bhusal, Chet Kant; Bhattarai, Sigma; Kunwar, Ankita; Shrestha, Saneep; Chhetri, Pradip; Priyanka, Jyoti (Journal of Nepal Health Research Council, 2024)
Background: Inappropriate, delayed and poor health seeking behavior increases the high risk of morbidity and mortality among newborns, infants and children. Newborns health status depends upon mothers’ health seeking behavior. This study aimed to determine the factors associated with mother’s health seeking behavior among newborn illness in Rupandehi District, Nepal. Methods: Community based cross-sectional study among 372 mothers aged 15-49 years was conducted in Rupandehi district Nepal from May to November 2019. Multistage probability random sampling was used as the sampling technique. Siddharthanagar municipality and Mayadevi rural municipality were selected randomly among 16 local units of Rupandehi district. Two wards from each unit were selected by stratified random sampling using non replacement lottery method. As the sample size was 372, ninety three respondents were selected randomly from each ward. Results: The mean age and standard deviation of mothers was 25.32±4.36 years respectively. Among 372 mothers, 21.24% had poor health seeking behavior. Mothers having more than one child (AOR=0.15; CI: 0.02-0.98), primary and above education (AOR=8.89; CI: 3.15-25.08), visited hospital after 24 hours of newborn illness (AOR=13.59; CI: 1.73-106.7), knew danger signs of newborn (AOR=18.74; CI: 5.65-62.23), practiced exclusive breastfeeding (AOR=8.20; CI: 3.36-20.03) were significantly associated with health seeking behavior.Conclusions: Almost 22 % of mothers had poor health seeking behavior regarding their newborn illness. Number of living child, education of mother, appropriate time for treatment, receive health services when there is dangers signs of newborn and exclusive breast feeding practice were independent factors associated with mother’s health seeking behavior. Hence, decision-makers and local administrator should provide specific intervention to newborns’ mother regarding family planning, identifying and preventing danger signs of newborn, importance of appropriate time of treatment and exclusive breastfeeding. Keywords: Health seeking behavior; illness; mother; newborn.